Mechanisms For Implementing Assessments in The Independent Curriculum: Analytical Study In Educational Institutions - Samin Samin (At-Tarbiyat, 2023)
The Merdeka Curriculum is an innovative concept in the world of education in Indonesia that aims to provide flexibility and freedom to teachers in designing more creative and innovative learning methods and materials. One of these things is the assessment process. Assessment in the Merdeka Curriculum refers to the evaluation process carried out to measure students' abilities and skills effectively, objectively, and accurately. Assessment aims to provide an overview of the extent to which students have achieved the competencies set out in the curriculum. In addition, assessment also provides feedback to students and teachers regarding student learning progress and assists in identifying weaknesses and strengths in teaching and learning. In its implementation, assessment or judgment plays an important role in the success of this successful program. The Merdeka Curriculum assessment itself is a series of activities carried out to determine the level of students' abilities in a lesson in the Merdeka Curriculum. The government has regulated learning and assessment in the Merdeka Curriculum in full and in detail. It is hoped that this regulated learning and assessment can serve as a reference for teachers in planning and implementing meaningful learning so that it can create more creative, critical thinking, and innovative students.